Orientocreadium elegans n. sp. and Orientocreadium pseudobagri Yamaguti (Digenea: Orientocreadiidae), from freshwater fish of the Primorsky region (southern far east, Russia) with a description of their life cycles - Besprozvannykh, Vladimir V.; Ermolenko, Alexey V.; Deveney, Marty R (Zootaxa, 2009)
Until recently only one species from the genus Orientocreadium was recorded from the southern part of the Primorye Region, far eastern Russia: O. pseudobagri Yamaguti. A new species, Orientocreadium elegans n. sp., was found recently in the yellow catfish, Pelteobagrus fulvidraco in rivers running into Khanka Lake and in the Arsenjevka River (part of the Ussuri River basin). It is distinguished from other species of Orientocreadium by possessing a body that is longer and narrower than Orientocreadium pseudobagri and shorter and narrower than Orientocreadium siluri and Orientocreadium chaenogobii. The suckers of O. elegans n. sp. are smaller than those of all other species of Orientocreadium and the pharynx is smaller than those of O. siluri and O. chaenogobii. Orientocreadium elegans n. sp. has spines on the cirrus and inside the metraterm and has the ovary in the posterior half of the body, differentiating it from O. siluri. Orientocreadiium elegans n. sp. has a cirrus sac that lies on the median line of the body dorsal to the ventral sucker, whereas the cirrus sac of O. pseudobagri passes laterally around the ventral sucker. Both trematode species use Lymnaea spp. snails as their first intermediate host, and tadpoles, freshwater fish and snails as the second intermediate host. The following fish have been recorded as definitive hosts in this region: the Amur sleeper, Perccottus glehni and P. fulvidraco for O. pseudobagri, and P. fulvidraco for O. elegans n. sp.